Parental supervision and sexual behaviour of adolescents in Brazil. (20th October 2021) - Sousa, M; Reis, G; Felisbino-Mendes, M
Abstract: Background: Sexual risk behaviors make adolescents more vulnerable to the main diseases, affecting their sexual health. The adoption of such behaviors may be related to the modes of supervision performed by parents, which is a factor that could minimize the adoption of such risky behaviors. Objective: To characterize parental supervision of Brazilian adolescents and estimate the prevalence of sexual risk behaviors in relation to the supervision received. Methods: Cross-sectional study that analyzed data from 102, 072 Brazilian adolescents who self-answered the National School Health Survey in 2015. We estimated the prevalence of parental supervision with their respective 95% confidence intervals, considering five indicators of parental supervision individually, and their simultaneity according to sex and sociodemographic characteristics. We also estimated the prevalence of sexual behaviours of adolescents: sex initiation, condom use at last intercourse, contraceptive use, mean age at first intercourse and number of partners, in relation to the supervision received. Results: One in seven Brazilian adolescents presented intense parental supervision, with the highest proportion among males (52.0%; 95%CI 50.6-53.4). White adolescents of both sex (39.7%; 95%CI 38.8-40.6), who do not work (39.1%; 95%CI 38.4-39.8), living with both parents (42.3%; 95%CI 41.4-43.1) and residing in the Midwest and South (39.7%; 95%CI 38.5-41.0) regions, showed greater parental supervision in relation to the others, also presenting lower sexual initiation and greater condom use. Moreover, the greater the simultaneity of the supervision indicators, the greater the prevalence of consistent condom use, use of contraceptive methods and lower average number of partners. Conclusions: We observed different patterns of parental supervision between boys and girls and according to sociodemographic characteristics. Moreover, the greater the supervision, the better the adolescents' sexual behaviors. Key messages: The results obtained point to the fundamental role of the family in providing adolescents with conditions that encourage healthy and risk-free sexual behavior, through supervision. The results obtained reveal gender inequalities in relation to the supervision of girls and boys.